Images of Soviet Lithuania for exile (1959-1990) - Mukaitė, Gabija (Vilnius University Open Series, 2021)
Those who left Lithuania during World War II were still interested in Soviet Lithuanian news. They received some of the news from letters, newspapers, radio, and television. The aim of this research is to analyse the images of Soviet Lithuania that were created through letters and visits to Lithuania from 1959 to 1990. The object of this work is the images of Soviet Lithuania for exile diasporas. Which was created by different sources of information. The problem of this research is that, there is not a lot of research about the communication by letters between people who stayed in Soviet Lithuania, and their relatives in exile. There is not a lot of research about emigrants who saw Lithuania during visits, and the images of it that they created themselves. The letters from relatives were controlled by KGB, and the messages that contained any sort of negative information about Lithuania, could not reach the recipients. However, occasionally, some letters containing negative information did reach diasporas, and it also painted a picture of the country. Struggles with money and the deficit of goods created the image of a lacking Lithuania, while social guarantees created a progressive image. Ambiguous images of Lithuania were also created through visits to Soviet Lithuania. It was due to different people that the visitors communicated with: thus, official and unofficial images were formed. The official images – shaped by such institutions as KGB – were progressive, while the unofficial ones – formed by the common people – denied some of the progressive images, because many people were suffering from the socialist regime. The governmental institutions were trying to hide these disagreeing images in particular. Consequently, depending on whom the visitors had contacted, they were able to create their own images of Lithuania.
Keywords: communication; letters; memories; exile; diaspora